Perwujudan Naskah Drama Anusapati Karya S.H. Mintardja dalam Pementasan Teater - Trias Untung Kurniawan (Institut Seni Indonesia Yogyakarta, 2016)
Seorang sutradara menentukan kualitas sebuah pementasan teater. Ia dituntut memiliki kepekaan dramatik sehingga dapat menerjemahkan sebuah naskah lakon menjadi pengalaman pentas yang berarti. Naskah lakon menjadi hal yang sangat penting dalam menghasilkan pementasan teater yang berkualitas. Penulis memilih naskah lakon Anusapati karya S.H. Mintardja untuk diwujudkan dalam sebuah pementasan teater. Lakon Anusapati adalah lakon yang tragis, bermula dari kesalahan yang dilakukan Ken Arok untuk mencapai keinginannya merebut kekuasaan. Kesalahan ini mengakibatkankarma yang tidak dapat ditolak oleh Ken Arok dan tujuh keturunannya. Naskah lakon Anusapati akan diwujudkan dalam sebuah pementasan dengan pendekatan ketoprak. Dengan mengawinkan konsep teater modern terhadap perkembangan ketoprak dengan memosisikan sutradara sebagai pusat kontrol atas segala aspek pemanggungan dengan tetap memberi ruang kepada para pemain untuk mengembangkan permainan secara maksimal. Dalam mewujudkan lakon menjadi sebuah pementasan membutuhkan konsep pemanggungan yang dapat dijadikan sebagai arah dalam menjalankan proses kreatif. Konsep pemanggungan memuat pokok-pokok gagasan yang akan diwujudkan dalam pementasan. Garis-garis permainan, desain artistik, dan musik pendukung dirancang untuk memenuhi terwujudnya gagasan. Sutaradara mengorganisasi seluruh aspek pemanggungan yang dikelola oleh beberapa staf artistik, seperti penata pentas, penata busana, penata rias, dan penata artistik sehingga menghasilkan pementasan yang menarik, berkualitas, dan layak untuk ditonton. The Embodiment of the Anusapati Script by S.H. Mintardja in Theatrical Staging with the Ketoprak Approach. Director determines the quality of a theatrical production. The Director is required to have dramatic sensibility (sense of dramatic) so that he can translate a script of the play being performed that may experience meaning. The script of the play becomes the thing that is very important in producing the quality of theatrical staging. The script of the play that becomes the choice of the author in a theatrical staging is the Anusapati by SH Mintardja. The Anusapati is a tragic screenplay, it starts from the mistakes done by Ken Arok in accomplishing his desire in seizing power. The mistakes result in karma that cannot be denied by Ken Arok and seven offspring. The script of Anusapati would be performed in a theatrical staging with the ketoprak approach. It is done by combining the concepts on modern theater and the development of ketoprak by positioning the director as the central of controlling over all aspects of staging by keeping on giving the space to the players to develop their performance to the maximum. In realizing the play becomes a staging, it needs the concept of staging that can serve as the creative process in the running direction. The concept of staging contains ideas which will be embodied in the idea of staging. Rules of play, artistic design, and music accompaniment are designed to meet the realization of the idea. The director organizes all aspects of staging that is maintained by some of the artistic staffs, such as a stage manager, a fashion stylist, a make-up stylist, and an artistic director and finally produce an interesting and qualified staging, and worthy to watch.